Identities Involving q-Bernoulli and q-Euler Numbers - D. S. Kim; T. Kim; J. Choi; Y. H. Kim (Abstract and Applied Analysis)
We give some identities on the q-Bernoulli and q-Euler numbers by using p-adic integral equations on ℤp.